Adaptive saturation system for grid-tied inverters in low voltage residential micro-grids - Bonaldo, Jakson P.; Paredes, Helmo K.M. [UNESP]; Costabeber, Alessandro; Pomilio, Jose A. (Institute of Electrical and Electronics Engineers (IEEE), 2015)
Provision of ancillary services, like power quality improvement is a key to attain higher utilization of multifunctional grid-tied inverter. However, the power quality improvement is mainly limited by the power capacity the grid-tied inverter. This paper explores integration issues of the next-generation intermittent power sources. In particular, two different strategies for enhancing power quality given the residual power capacity of the inverters are developed. One strategy aims to obtain the expected power quality exploiting the dynamic saturation of the inverter rated apparent power and another strategy is based on peak current detection. Both strategies offer the possibility to generate appropriate references for the inner current control loop. The two proposed strategies are compared in performance, and a discussion on their practical implementation for the best performance of the inverters is provided.
Keywords: conservative power theory; multifunctional grid-tied inverter; power quality; smart micro-grid